2018
DOI: 10.1002/joc.5523
|View full text |Cite|
|
Sign up to set email alerts
|

Climatology of sea breezes along the Red Sea coast of Saudi Arabia

Abstract: Long‐term near‐surface observations from five coastal stations, high‐resolution model data from Modern Era Retrospective‐Analysis for Research and Applications (MERRA) and high‐resolution daily sea surface temperature (SST) from National Ocean and Atmospheric Administration (NOAA) are used to investigate the climatology of sea breezes over the eastern side of the Red Sea region. Results show existence of separate sea breeze systems along different segments of the Red Sea coastline. Based on the physical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 64 publications
5
17
0
Order By: Relevance
“…Corkscrew sea breezes may initiate in the presence of smaller thermal contrasts than other LSBC types. This facilitation of LSBC initiation is consistent with the climatological study of sea breezes over the Saudi Peninsula conducted by Khan et al (2018), who also found that the frequency of sea breeze occurrences increased from north to south. Differences in the mean-flow/coastline orientation over the East African side of the Red Sea resulted in gradient winds flowing roughly parallel to the coast and to the right of this flow.…”
Section: Mean Lower Tropospheric Flow and Influences Upon The Lsbcsupporting
confidence: 90%
See 1 more Smart Citation
“…Corkscrew sea breezes may initiate in the presence of smaller thermal contrasts than other LSBC types. This facilitation of LSBC initiation is consistent with the climatological study of sea breezes over the Saudi Peninsula conducted by Khan et al (2018), who also found that the frequency of sea breeze occurrences increased from north to south. Differences in the mean-flow/coastline orientation over the East African side of the Red Sea resulted in gradient winds flowing roughly parallel to the coast and to the right of this flow.…”
Section: Mean Lower Tropospheric Flow and Influences Upon The Lsbcsupporting
confidence: 90%
“…Seasonal land-sea temperature differences reversed sign for fall and winter, while a land-sea surface pressure gradient favorable for onshore flow was maintained year round (not shown). Fall and winter patterns have been shown in related studies by Khan et al (2018), Qian et al (2009), and Rotunno (1983) to be quasi-antitriptic, that is atmospheric flow based only on frictional forces and a local pressure gradient developing from uneven heating (prone to occur at latitudes less than 30°).…”
Section: Seasonalitymentioning
confidence: 94%
“…Along the Red Sea coast, the wind direction was mostly western, throughout the whole year, accounting for the effect of the Soudan Low from October to May and the establishment of the sea breeze. Sea breeze in the Northerly/North Westerlies direction developed in the Red Sea and penetrated 10-20 km inland [40]. The wind direction pattern was more complicated in the regions of Asir and Jizan, due to the complex terrain.…”
Section: Wind Speed and Directionmentioning
confidence: 99%
“…At a larger temporal scale, the climatological studies of Azorin-Molina and Chen (2009) and Azorin-Molina et al (2011) point out the importance of the larger-scale winds on the SB features, through the inspection of the onset and duration of the SB in the eastern Iberian Peninsula. There are SB studies based on remote sensing observations, inspecting the convection associated through the visible channels of satellite or more recently in Khan et al (2018) where the temperature difference between land and sea is evaluated through satellite-derived surface temperatures. Aircraft observations (Finkele et al, 1995) are also taken to further understand the SB circulation cell.…”
Section: Introductionmentioning
confidence: 99%